Prediction of Pulmonary Embolism Extent by Clinical Findings, D-dimer Level and Deep Vein Thrombosis Shown by Ultrasound - Galle, Cécile; Papazyan, Jean-Pierre; Miron, Marie-José; Slosman, Daniel; Bounameaux, Henri; Perrier, Arnaud (Thrombosis and Haemostasis, 2001)
Pulmonary embolism (PE) may encompass a wide spectrum of severity. To determine whether clinical findings, D-dimer (DD) concentration, and deep vein thrombosis (DVT) shown by lower-limb venous compression ultrasonography (US) might predict the scintigraphic extent of PE, we studied 104 hemodynamically stable consecutive outpatients with acute PE diagnosed by a high-probability ventilation-perfusion lung scan. Scintigraphic extent of PE was classified into three categories: perfusion defects corresponding to <30%, 30–50%, or >50% of the total lung area. Median respiratory and heart rates were found to be significantly related to the extent of PE. Higher median alveolar-arterial oxygen difference values were observed as the proportion of lung perfusion defects increased (>50% vs. <30%, 6.3 vs. 3.6 kPa, P <.0001). Median plasma DD concentration was 7950 g/L in patients with >50% perfusion defects compared to 2731 g/L in those with <30% defects (P = .0001). DD levels above 4000 g/L were associated to more extensive perfusion defects (>50% vs. <30% defects, OR 30; 95% CI 5.8–155). Finally, a proximal DVT was more likely among patients with larger perfusion defects (>50% vs. <30% defects, OR 4.5; 95% CI 1.5–13.6). In conclusion, clinical signs such as tachypnea and tachycardia, alveolar-arterial oxygen difference, plasma DD concentration, and presence of DVT on US are predictors of a larger PE, as assessed by the extent of perfusion defects on high probability lung scans.
Keywords: Pulmonary embolism; lung scan; prognosis